SELECTION OF CHARACTERS THROUGH ESTIMATION OF GENETIC PARAMETERS, ASSOCIATION AND PATH ANALYSIS IN SWEET CORN (Zea mays L. saccharata) - D.BHADRU; B. MALLAIAH; V. SWARNALATHA; G. ANURADHA (The Bioscan, 2020)
Present study was aimed to detection of green cob yield and yield attributing traits for identification of high yielding sweet corn genotypes. Green cob yield (0.62,54.74), TSS (0.67,24.81), days to 50% pollen shedding (0.93, 26.82) and silking (0.89, 25.06) had recorded high heritability together with high genetic advance % of mean which suggests that these traits are mainly under the control of additive gene action and selection may be effective. At genotypic and phenotypic level green cob yield registered positively significant correlation with plant height (0.6565, 0.8609), cobs/plot (0.6346, 0.7853) and days to 50% silking (0.0518, 0.1308) and negatively with TSS (-1.1637, -0.2102). Path analysis studies reveled that all the characters recorded low magnitude of direct effects on the green cob yield.